Chronic Infiltration of T Lymphocytes into the Brain in a Non-human Primate Model of Parkinson's Disease. (1st April 2020) - Seo, Jincheol; Park, Junghyung; Kim, Keonwoo; Won, Jinyoung; Yeo, Hyeon-Gu; Jin, Yeung Bae; Koo, Bon-Sang; Lim, Kyung Seob; Jeong, Kang-Jin; Kang, Philyong; Lee, Hwal-Yong; Choi, Won Seok; et al.
Highlights: Brains of non-human primates induced by with MPTP showed chronic infiltration of T-cells. T-cells were observed in close proximity to dopaminergic neurons of the non-human primates Parkinson's disease model. DAT expression was found on infiltrated CD4+ and CD8+ T-cells. Chronic normalization of serum RANTES was observed in non-human primates after MPTP injection. Altered microglial morphology was found in the chronic phase after MPTP injection. Abstract: Study of interactions between the nervous system and immunity offers insights into the pathogenesis of Parkinson's disease (PD) and potential therapeutic strategies for neurodegenerative diseases. Studies on rodents have revealed regulatory mechanisms of microglial activation and T lymphocyte recruitment in PD. However, the mechanisms underlying chronic T lymphocyte infiltration into the brain after 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) injection into a non-human primate (NHP) model of PD remain unknown. This study aimed to investigate changes in serum RANTES (regulated on activation, normal T cell expression and secretion) and analyze the chronic infiltration of T lymphocytes into the brain and microglia activation in NHPs at 48 weeks post-MPTP administration. We found selective and local chronic infiltration of CD4+ and CD8+ T lymphocytes, loss of dopaminergic neurons, dopamine transporter expression, chronic normalization of RANTES in the peripheral blood, and altered microglial morphology at 48 weeks after MPTP injection. This study confirms the involvement of CD4+ and CD8+ T lymphocyte infiltration in MPTP-induced NHP models of PD. Additionally, we corroborated previous findings regarding the mechanisms of T lymphocyte-induced neurodegeneration. The findings of chronic infiltration of T lymphocytes in our NHP model of PD provide novel insights into PD pathogenesis and the development of preventive and therapeutic agents.